Development and evaluating content validity of clinical skill analysis index tools - Jamaludin, Thandar Soe Sumaiyah; Nurumal, Mohd. Said; Ahmad, Norfadzilah; Muhammad, Siti Aeshah @ Naznin; Chan, Chong Mei (Scientific Foundation SPIROSKI, 2022)
BACKGROUND: The current structured nursing clinical skill assessment checklist is steps driven and the soft skills component is fragmented and limited. AIM: This study aimed to evaluate the face and content validity of a tool that had been developed to assess the current structured clinical skill assessment for the Malaysian undergraduate nursing program. METHODS: The face and content validity of the instrument were examined based on the opinions of experts. The item content validity index and scale content validity index (S-CVI) were calculated by using the mean approach and inter-rater agreement. The content validity of the instrument was assessed by S-CVI/UA and S-CVI/Ave. The scale was revised based on comments from a panel of eight experts in the first review stage and thereafter, evaluated by another group of three experts in the second review stage. RESULTS: There were nine soft skills elements identified for the clinical skill analysis index (CSAI) tools in this study. Those were communication skill, social skill and responsibility, critical thinking skill, problem-solving skill, teamwork, leadership skill, professional and ethical decision-making skill, numeracy skill, and interpersonal skill. The findings at the face validity stage yielded ten domains with eight nursing core procedures areas being retained, based on 95% or more agreement from expert responses. The result of S-CVI/UA and S-CVI/Ave of the CSAI tools yielded scores of 0.91 and 1 respectively. CONCLUSION: Findings indicated that this instrument had an excellent face and content validity to assess the current structured clinical skill assessment for the Malaysian undergraduate nursing program.